ANALISIS KENAIKAN SISA LEBIH PERHITUNGAN ANGGARAN PEMERINTAH KABUPATEN REMBANG TA 2011-2015 DITINJAU DARI PERENCANAAN DAN PELAKSANAAN ANGGARAN - Mochamad Setyo Budi (ABIS: Accounting and Business Information Systems Journal, 2017)
The amount of the budget surplus (SILPA) of the Government of Rembang District increased in the fiscal year (FY) of 2011-2015. In the FY 2015, the SILPA reached even as much as 26,78% of the local revenue and expenditure budget (APBD). The increase was hihgly contradictory to the budgeting process, considering that in the budgeting process, considering that in the budgeting process, the District Government implemented a deficit-based budgeting system with the SILPA budget at nil. This study was to determine the causes of the increase in the SILPA of the Government of Rembang District in the FY of 2011-2015. This was qualitative research with a case study approach. It involved participants from three elements whose jobs are connected to the local government financial management, namely the budget managers, budget users, and Budget Agency of the Regional House of Representative (DPRD). The results of this study indicate that the increase in the SILPA of the Government of Rembang District occurs when the budget is in surplus, and the net financing is te positive. The budget estimated to the accommodate the use of the SiLPA of the previous year as mandate by the regulation of the Minister of Home Affairs Number 13 of 2006 where in principle, some of the programs and/or activities have no longer implemented. Second, agency problem causes both the application of the minimal approach pattern in the process of determining the income estimation and the aplication of the maximal approach pattern in the process of determining the expenditure allocation result in the budgetary slack. Third, the legal cases ensnaring some officials of the Government of Rembang District have made the employees not sufficiently perform in the absorbing the budget.